Characteristics of rain cells over the northwest Pacific warm pool - Ping Ye; Aoqi Zhang (Meteorologische Zeitschrift)
The importance of precipitation morphology has been emphasized by recent studies. However, the specific morphological characteristics of rain cells (RCs) and their impact on rainfall intensity over the oceans remain unclear. In this study, using 15-year observations from Tropical Rainfall Measurement Mission (TRMM) Precipitation Radar (PR), more than 600 thousand RCs in the northwest Pacific warm pool were identified and approximated by rectangle. The results showed that the horizontal scale of RCs was negatively correlated with their occurrence frequency, while there was a logarithmic correlation between the length and width of the approximated rectangle. The morphology of RCs presented huge zonal differences but small meridional differences over the study region. RCs had larger scale, narrower 2-D shape, and slender 3-D shape in the southern region compared with ones in the northern region. Precipitation intensity generally increased with the enlargement of the horizontal scale. The relationships between precipitation intensity and shape of RCs were very complex. Moderate shape of RCs had the weakest precipitation, whereas 2-D narrower or 3-D slender RCs had the strongest precipitation. The results would be helpful for monitoring and predicting precipitating clouds over the oceans.